Not quite white white trash and the boundaries of whiteness - Wray, Matt 1964- (Duke University Press, 2006)
Introduction: White trash as social difference : groups, boundaries, and inequalities -- Lubbers, crackers, and poor white trash : borders and boundaries in the colonies and the early republic -- Imagining poor whites in the antebellum South : abolitionist and pro-slavery fictions -- "Three generations of imbeciles are enough" : American eugenics and poor white trash -- "The disease of laziness" : crackers, poor whites, and hookworm crusaders in the new South -- Limning the boundaries of whiteness
Includes bibliographical references (p. [181]-210) and index
Keywords: Whites / Race identity / United States; Whites / Public opinion / United States; Rural poor / Public opinion / United States; Stereotypes (Social psychology) / United States; Difference (Psychology); Social stratification / United States; Social classes / United States; Public opinion / United States